Systems-Level G Protein-Coupled Receptor Therapy Across a Neurodegenerative Continuum by the GLP-1 Receptor System - Janssens, Jonathan; Etienne, Harmonie; Idriss, Sherif; Azmi, Abdelkrim; Martin, Bronwen; Maudsley, Stuart (Frontiers in Endocrinology, 2014)
With our increasing appreciation of the true complexity of diseases and pathophysiologies it is clear that this knowledge needs to inform the future development of pharmacotherapeutics. For many disorders the disease mechanism itself is a complex process spanning multiple signaling networks, tissues and organ systems. Identifying the precise nature and locations of the pathophysiology is crucial for the creation of systemically-effective drugs. Diseases once considered constrained to a limited range of organ systems, e.g. central neurodegenerative disorders such as Alzheimer’s disease (AD), Parkinson’s disease (PD) and Huntington’ disease (HD), the role of multiple central and peripheral organ systems in the etiology of such diseases is now widely accepted. With this knowledge, it is increasingly clear that these seemingly distinct neurodegenerative disorders (AD, PD and HD) possess multiple pathophysiological similarities thereby demonstrating an inter-related continuum of disease-related molecular alterations. With this systems-level appreciation of neurodegenerative disease it is now imperative to consider that pharmacotherapeutics should be developed specifically to address the systemic imbalances that create the disorders. Identification of potential systems-level signaling axes may facilitate the generation of therapeutic agents with synergistic remedial activity across multiple tissues, organ systems and even diseases. Here we discuss the potentially therapeutic systems-level interaction of the glucagon-like peptide 1 (GLP-1) ligand-receptor axis with multiple aspects of the AD, PD and HD neurodegenerative continuum.